Coupling Aquaponic Systems with Sustainable Energy and Food Generation: A Review (LACCEI, 2024)
Nowadays society faces different problems regarding populational growth, energetic consumption increase, and food shortages currently more than 66% of the world population is undernourished. Additionally, present-day food production is becoming constrained due to the scarcity of arable land, freshwater, and the chemical contamination of fertilizers. This scarcity of resources is increasing along with the rapid growth of the human population around the world. This paper performs a systematic review via a bibliometric analysis employing VOSviewer, observing and analyzing scientific research trends in terms of sustainable food and energy generation. We present diverse aquaponic systems and their survival and efficiency rates. In terms of energetic generation, we discuss on the possibility of employing a plant micro fuel cell (P-MFC) with Oryza sativa to power up, resulting in the harvest of both rice and spinach. In terms of fish, the Oreochromis niloticus was selected due to its adaptability, survival rate, and local presence. Additionally, in the context of the scarcity of freshwater, we propose employing saline water in our system.